Virtual and remote labs in education: A bibliometric analysis. (July 2016) - Heradio, Ruben; de la Torre, Luis; Galan, Daniel; Cabrerizo, Francisco Javier; Herrera-Viedma, Enrique; Dormido, Sebastian
Abstract: Laboratory experimentation plays an essential role in engineering and scientific education. Virtual and remote labs reduce the costs associated with conventional hands-on labs due to their required equipment, space, and maintenance staff. Furthermore, they provide additional benefits such as supporting distance learning, improving lab accessibility to handicapped people, and increasing safety for dangerous experimentation. This paper analyzes the literature on virtual and remote labs from its beginnings to 2015, identifying the most influential publications, the most researched topics, and how the interest in those topics has evolved along the way. To do so, bibliographical data gathered from ISI Web of Science, Scopus and GRC2014 have been examined using two prominent bibliometric approaches: science mapping and performance analysis. Graphical abstract: Highlights: Laboratory experimentation plays an essential role in engineering and sci-entific education. Virtual and remote labs are emerging as a valuable alternative to conven-tional hands-on labs. This paper analyzes the literature on virtual and remote labs from 1993 to 2015. 4405 records retrieved from ISI Web of Science, Scopus and GRC2014 are processed. Two bibliometric approaches are applied: performance analysis and science mapping.